Infographic. Head to toe considerations for the postpartum endurance athlete - Afifi, T.; Barrack, M. T.; Casey, E.; Huddle, M.; Kliethermes, S. A.; Kraus, E.; Toresdahl, B. G.; Wasfy, M. M.; Tenforde, A. S. (British Journal of Sports Medicine, 2024)
The physical and psychological changes in the postpartum athlete directly impact their ability to return to sport post partum. Understanding the unique challenges and considerations surrounding the postpartum endurance athlete is essential to optimise health outcomes for both the athlete and the newborn.